Empat Landasan Konseling Islam Dalam Alquran - Hadini, Hadini; Imamuddin, M. (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2023)
Problems of psychology eventually faced in the Islamic education field. This fact makes student have to use counseling to solve their problem, but, actually general counseling can’t overcome this problem, therefore, the comprehension of Islamic educational counseling is based on Al-Qur’an and Sunnah. In this study, the researcher used library research as a method, in which, literature, books, and journals both national and international as a resource of data, this resource is related to the topic, especially the study of general theory as a base in developing Islamic educational counseling in Al-Qur’an and sunnah will be analysis by researcher. The result of this study found that some of the concepts of Islamic educational counseling based on Al-Qur’an and sunnah, some of the indicate of the human inner is: the first, Al-Qur’an and sunnah support us to research human psychological phenomena, the second, Al-Qur’an and sunnah was mentioned psychological potential of human, the third, Al-Qur’an and sunnah has mentioned the effects as a result of action and doing of human, the fourth, Al-Qur’an and sunnah support us to overcome the psychological problems of human with counseling process, the fifth, Al-Qur’an, and sunnah says that Allah is the only one the source of happiness.